ANALISIS ISI TOPIK DISKUSI INTERAKTIF MAHASISWA UNIVERSITAS TERBUKA DALAM FITUR â€œFORUM KOMUNITAS UT ONLINEâ€ (Content Analysis Interactive Discussion Topic Open University in Fitur â€œForum Komunitas UT Onlineâ€) - Daulay, Pardamean (Institute of Research and Community Outreach - Petra Christian University, 2008)
One of problems faced by institution which carries out long distance learning system is lack interaction between students with lecturer. To solve this problems, universitas terbuka (UT) where media internet condeneted a facility of community forum service in UT website. This research aim is to descript UT student interaction pattern in community forum, during registration 06.2 until 07.1. This research is using qualitative description by applying content analysis approach. Result of research shows that there are 1201 email, with 1293 problem, which submitted by 479 students, the most intensive problem is interaction personal (25,90%), general issue (14,24%) score or examination (11,91%), tutorial (25,90%), module (6,58%), learning material substance (4,08%), the way learning (4,08%), TAP/UKP (4,00%), TM/ML (3,41%), registration (3,41%), graduation (2,33%), curriculum (1,58%), accreditation (1,58%), scholarship (0,92%), school fee (0,58%), credit switching (0,42%), and diploma (0,17%).